Language Contestation of Tourism Spots at Braga Street, Bandung (A Linguistic Landscape Study) - Azzahro, Septia Sekar Madji; Permanaludin, Udayana; Ardiansyah, Erlan Aditya (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2025)
Braga Street, Bandung serves as a public space with multilingual activity namely language contestation, showcasing the intersection of historical, cultural, and modern linguistic influences. This study examines the dynamics of language use on Braga Street, where Sundanese, Indonesian, and English coexist and compete in public signage, business communication, and cultural expressions. The method used is the mixed method called explanatory sequential design method with photograph data collecting method and interviews done with five shopkeepers. The result shows that English domination in sign is unbearable although the law regulates the language used in public space. English serves the purpose as a common language and a global language, supported by shopkeepers' statements using English made it easier for customers to locate their stores. As a result, Westernization has been a significant driving force behind the signs. This research highlights how language act as a tool for preserving local wisdom and embracing modernization.